KAJIAN YURIDIS MENGENAI PERSAINGAN USAHA ANTARA USAHA MIKRO, KECIL, MENENGAH (UMKM) DENGAN MINIMARKET - Suhartono, Alfian Priyo; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013, 2013)
Minimarket is a form of franchising is very easy to find as Alfamart, Indomaret, and Circle K, and many others, the judicial review of competition among Micro, Small and Medium Enterprises (SMEs) with Minimarket aims to determine whether the rules on competition the Micro, Small and Medium Enterprises (SMEs) with the Minimarket is adequate or not. It turns out there are still shortcomings in the Act Number 5 of 1999 concerning Prohibition of Monopolistic and Unfair Business Competition specifically regulating the pricing agreement and the appointment of a supplier.
Keywords: Minimarket, Franchise, SMEs, Unfair Business Competition